/ THE ASSOCIATION OF COMMON GST POLYMORPHISMS WITH INFLAMMATORY AND MULTIORGAN IMPAIRMENT BIOMARKERS IN COVID-19 - Jerotić, Djurdja; Krunić, Ana (Medicinski podmladak, 2023)
Introduction: Due to the established role of oxidative stress in the pathophysiology of COVID-19, it has been proposed that inter-individual differences in patients’ clinical manifestations might be affected by variations in genes encoding antioxidant enzymes, such as glutathione S-transferases (GSTs). Aim: The aim of this study was to assess the association of polymorphisms in cytosolic GSTs (GSTA1 rs3957357, GSTM3 rs1332018 and GSTP1 rs1695) with inflammatory parameters (leukocytes, lymphocytes, monocytes, CRP, fibrinogen, ferritin) and multiorgan impairment biomarkers (urea, creatinine, AST, ALT, LDH) in COVID-19 patients at two time points. Materials and Methods: GSTM3, GSTA1 and GSTP1 genotypes were determined in 150 COVID-19 patients by appropriate PCR methods. Results: Inflammatory biomarkers (leukocytes, lymphocytes, monocytes) increased 7 days upon admission to the hospital (p<0.001), while CRP and fibrinogen decreased (p<0.001). Out of five analysed multiorgan impairment biomarkers, only urea increased significantly 7 days upon admission (p<0.007), while AST showed statistically significant drop (p<0.001). COVID-19 patients homozygous for variant GSTM3*C/C genotype had increased levels of inflammatory biomarkers such as CRP, fibrinogen and ferritin, but the borderline significance was observed only for fibrinogen (p=0.057). COVID-19 patients homozygous for variant GSTM3*C allele had the highest levels of ALT (p=0.021) and LDH (p=0.045) upon admission. Conclusion: Our results on the association between GSTM3 variant genotype with parameters of systemic inflammation and liver damage in COVID-19 patients can contribute to further understanding of pathophysiological mechanisms underpinning this disease, as well as early recognition of COVID-19 patients prone to worse course of the disease.